2021
DOI: 10.4103/jcar.jcar_20_20
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like protein 4 is a chromatin-bound protein that enhances mammosphere formation in vitro and experimental triple-negative breast cancer brain and liver metastases in vivo

Abstract: INTRODUCTION: Metastatic progression in triple-negative breast cancer (TNBC) patients occurs primarily because of nuclear reprogramming that includes chromatin remodeling and epigenetic modifications. The existing and most successful chemotherapies available for metastatic TNBC target nuclear proteins or damage DNA. The objectives here are to investigate an undescribed role for the molecular biology of nuclear angiopoietin-like protein 4 (ANGPTL4) and to characterize the effect of ectopic overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Cryosections were prepared and stained for the CSC marker CD44 and examined under a fluorescent microscope (Figure 4). Other reported CSC markers were investigated, including GD2, 26 CD133, CD24, and ANGPTL4 27 . CD44 was chosen because of its prevalence in pan‐cancer CSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryosections were prepared and stained for the CSC marker CD44 and examined under a fluorescent microscope (Figure 4). Other reported CSC markers were investigated, including GD2, 26 CD133, CD24, and ANGPTL4 27 . CD44 was chosen because of its prevalence in pan‐cancer CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Other reported CSC markers were investigated, including GD2, 26 CD133, CD24, and ANGPTL4. 27 CD44 was chosen because of its prevalence in pancancer CSCs. Dual-or triple staining was not adopted to avoid the high occurrence rate of false negatives.…”
Section: Cscs Are Enriched In Paratumors Of Lower Electrostatic Poten...mentioning
confidence: 99%
“…This study contributed to our understanding of the behavior of nanomaterials in plants. Determining the transformation of metal-based nanoparticles in plants, like other types of nanoparticles (such as polymer nanomaterials and carbon nanomaterials), is difficult because of the substantial background of the plant matrix and the shortage of effective approaches of spotting [112][113][114][115]. Although, there is no study which revealed the biotransformation of these nanomaterials in plants, this potential deformation should not be ignored [116][117][118][119][120][121][122].…”
Section: Biotransformation Of Nanomaterials In Plantsmentioning
confidence: 99%
“…Breast cancer (BC) is one of the leading causes of mortality as well as the most prevalent type of cancer in women worldwide [1][2][3]. BC seems to be the cause of 18.2% of all cancer deaths, 16.2% of all female cancers, and 22.9% of invasive cancers [4].…”
Section: Introductionmentioning
confidence: 99%